2018
DOI: 10.1002/adsc.201800191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Piperidine Derivatives by Rhodium‐ Catalyzed Tandem Reaction of N‐Sulfonyl‐1,2,3‐Triazole and Vinyl Ether

Abstract: A chemoselective tandem reaction of 4acyloxymethylene-1-sulfonyl-1,2,3-triazole and vinyl ether was reported, producing polysubstituted piperidine derivatives in up to 96% yield. The key intermediate N-sulfonyl 1-azadiene generated by migration of the OAc group to the a-imino rhodium carbene was isolated and a plausible mechanism was proposed. Several related ring systems were constructed from the highly functionalized products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In 2015, Murakami, Anbarasan, and Chen almost simultaneously reported a method to synthesize tryptamine derivatives employing C3‐nonsubstituted indoles and 1‐sulfonyl‐1,2,3‐triazoles. In addition to this, Shi, Anbarasan, and our group found that 1‐sulfonyl‐1,2,3‐triazoles can also serve as aza‐[4 C] units in some special cases (Scheme c). In these cases, the 1,2‐sulfur (or OAc) migration of an α‐imino rhodium carbene delivers an α,β‐unsaturated imine, which can participate in the ring formation reaction as an aza‐[4 C] synthon.…”
Section: Figurementioning
confidence: 81%
“…In 2015, Murakami, Anbarasan, and Chen almost simultaneously reported a method to synthesize tryptamine derivatives employing C3‐nonsubstituted indoles and 1‐sulfonyl‐1,2,3‐triazoles. In addition to this, Shi, Anbarasan, and our group found that 1‐sulfonyl‐1,2,3‐triazoles can also serve as aza‐[4 C] units in some special cases (Scheme c). In these cases, the 1,2‐sulfur (or OAc) migration of an α‐imino rhodium carbene delivers an α,β‐unsaturated imine, which can participate in the ring formation reaction as an aza‐[4 C] synthon.…”
Section: Figurementioning
confidence: 81%
“…They reacted ( N -tosyl-1,2,3-triazol-4-yl)­methyl acetates 162.1 with different coupling partners such as alkyl vinyl ethers 162.2 and various substituted indoles 162.5 in the presence of a rhodium catalyst (Scheme ). , These reactions afforded piperidines 162.4 and pyrido­[2,3- b ]­indole derivatives 162.6 through aza-Diels–Alder reaction of the in situ -generated aza-1,3-dienes 162.3 . Simultaneously, they explored the reaction between benzoxy-tethered N -sulfonyl-1,2,3-triazoles 162.7 and indoles 162.8 , which afforded cyclopenta­[ b ]­indoles 162.9 in good to moderate yields .…”
Section: Denitrogenative Transformations Of Triazolesmentioning
confidence: 99%
“…When the alkoxy group is absent, the corresponding α‐substituted β‐enaminone 63 is obtained, [89] and when present, the aldehyde moiety of 64 is rapidly transformed into the corresponding imine 65 , which spontaneously makes an intramolecular nucleophilic attack on the secondary amine, and, as a result, 1,2,3,4‐tetrahydropyridine motifs are obtained [90–94] . Given that several methods involving catalysts to prepare tetrahydropyridines using parent substrates have been reported, [95–98] the high reactivity of the push‐pull system on these fluorinated β‐enaminones 65 may be the main cause for the spontaneous cyclization observed.…”
Section: Synthesis Of Tetrahydropyridines Using Acylated 2‐alkoxy‐34‐dihydro‐2h‐pyransmentioning
confidence: 99%